Fe2O3 nanoparticles disrupt microstructure and reduce the viscoelasticity of simulated asthma airway mucus for potential airway mucus clearance applications - Zhong, Jiayuan; Shi, Lei; Liu, Zhiwei; Ni, Kai; Liu, Lei; Pan, Yan; Li, Jingjing; Yu, Xiaowei; Deng, Linhong; Luo, Mingzhi (Frontiers in Physiology, 2025)
Fe2O3 nanoparticles have been developed as carriers to transport drugs through airway mucus (AM); however, their impacts on the rheological properties of AM, especially in disease states, are unknown. In this study, we investigated the abilities of Fe2O3 nanoparticles dispersed in various media to alter the microstructure and rheological behaviors of simulated asthmatic AM. Here, the simulated AM was prepared via reconstituted mucins and other components in a composition resembling that of human AM reported in asthma, followed by treatment with Fe2O3 nanoparticles before and after curing. Subsequently, the AM samples treated with and without Fe2O3 nanoparticles were examined for their microstructures by optical immunofluorescence microscopy and for the rheological behaviors via steady-state and dynamic rotational rheometry. The results indicate that the Fe2O3 nanoparticles disrupt the mucus microstructure by inducing protein aggregation to increase the pore size and fiber diameter of the AM. However, the Fe2O3 nanoparticles significantly reduced the magnitudes of the viscoelastic properties of AM, including apparent viscosity, yield stress, and dynamic viscoelastic modulus. Although the addition of Fe2O3 nanoparticles before and after curing of AM appeared to produce similar effects, these effects had greater magnitudes when the nanoparticles were added before curing. The effects were also dependent on the concentration and surface property determined by the dispersion medium of the nanoparticles; accordingly, Fe2O3 nanoparticles dispersed at a concentration of 0.4 mg/mL in H2O were the most potent at altering the microstructure and rheology of AM, producing better results than the concentration of 0.4 mg/mL of the conventional mucolytic chymotrypsin. Furthermore, tests on mucus samples collected from asthmatic patients showed similar results to those obtained with the simulated AM. Together, these findings suggest that Fe2O3 nanoparticles per se are useful as not only drug carriers but also expectorant agents for AM clearance therapy; they may also be more beneficial than pharmaceutical mucolytics owing to their wide availability and high biocompatibility.